You Are Old, but Are You Out? Intergenerational Contact Impacts on Out-Group Perspective-Taking and on the Roles of Stereotyping and Intergroup Anxiety - Long, Yanxi; Jiang, Xinxin; Wang, Yuqing; Zhou, Xiaoyu; You, Xuqun (Frontiers in Psychology, 2022)
Perspective-taking (PT) is an important ability to imagine the world from another’s point of view. Prior studies have shown that younger adults are more likely to consider the opinions of age-based in-group members relative to out-group members. However, the cause of this priority is still unknown. We conducted three independent studies to explore the effect of intergenerational contact on younger adults’ PT toward older adults and the possible roles of stereotyping and intergroup anxiety. A total of 192 college students completed the Perspective taking Scale in Study 1 after being primed with age-based intergroup relationships. The results indicated that younger adults found it more difficult to take the perspective of older adults than that of their peers. 200 college students completed the Prior Contact Scale, Intergroup Anxiety Scale, Negative Stereotype Scale, and PT Scale in Study 2. The results demonstrated that intergenerational contact improved PT toward older adults by disrupting negative stereotypes, and intergroup anxiety moderated this mediating relationship. A total of 215 college students completed the PT Scale in the context of imagining intergenerational contact in Study 3. Interestingly, imagined contact effectively increased younger adults’ ability to take older adults’ perspectives. The present research verifies that contact is important for influencing younger adults’ emotional (intergroup anxiety) and attitudinal (stereotyping) factors that are critical to improving younger adults’ ability to take older people’s perspectives. This is of great significance for developing harmonious intergenerational relationships.